REFORMASI BIROKRASI MELALUI PENATAAN KELEMBAGAAN PADA SEKRETARIAT DAERAH KOTA KENDARI - Muhammad Basri (Universitas Halu Oleo, 2018)
ABSTRACTThe purpose of this study was to determine : (1) Implementation of Bureaucratic Reform through Institutional Arrangement at the Regional Secretariat of Kendari City, (2) Factors Affecting the Implementation of Bureaucratic Reform Through Institutional Arrangement at the Regional Secretariat of Kendari City. The location of this study is the Regional Secretariat of Kendari City, Jl. Drs. H Abdullah Silondae No. 8 Kendari City. The type of this study is Qualitative Description. The informants in this study were 6 people who were employees of the Regional Secretariat of Kendari City. Data collection techniques in this study were observation, interviews and document studies. Data Analysis techniques of the study were form of data collection, data reduction, data display or data presentation, and drawing conclusions. The results showed that the Implementation of Bureaucratic Reform through Institutional Arrangement at the Kendari City Secretariat was viewed from the dimensions of structur and culture (work culture) of the bureaucracy. Factors that influence the Implementation of Bureaucratic Reform in the Regional Secretariat of Kendari City are Effectiveness, Efficiency and Productivity of the Regional Devices Organization of Kendari City, the Process of Delegating Apparatus Authority to officials below, and Bureaucratic Culture. As a government actor, bureaucrats are expected to be able to run the bureaucratic arrangement as well as possible following the principles of reform proclaimed to achieve a clean, effective, efficient, productive and highly competitive bureaucracy in order to realize the bureaucratic reform that has been aspired so far. Keywords : Bureaucratic Reformation, Institutional Arrangement, Structure and Bureaucratic Culture